Subject integration in teaching Russian-English technical translation - Gillespie, David Ch (Антропоцентрические науки: инновационный взгляд на образование и развитие личности : материалы XII Международной научно-практической конференции, 17-18 декабря 2020 года)
this article argues for the importance of subject integration by presenting certain examples of the practical and professional translation of technical texts from Russian into English. It is intended to facilitate the teaching of technical translation to students at an advanced level of their instruction, including on Masters courses. It does not pretend to offer any theoretical perspectives or insights into translation theory, but rather highlights the need for contextualization in professional translation practice. And its pedagogical implications. The challenge of contextualization is demonstrated in the Russian lexis and syntax facing the translator into English. The register chosen is the translation of medical terminology, though the paradigms proposed may naturally apply to other technical texts